Coke Formation during Propane Dehydrogenation over Ga−Rh Supported Catalytically Active Liquid Metal Solutions. Issue 4 (7th January 2020) - Wolf, Moritz; Raman, Narayanan; Taccardi, Nicola; Haumann, Marco; Wasserscheid, Peter
Abstract: Supported Catalytically Active Liquid Metal Solutions (SCALMS) were recently described as a new class of heterogeneous catalysts, where the catalytic transformation takes place at the highly dynamic interface of a liquid alloy. Their application in alkane dehydrogenation has been claimed to be superior to classical heterogeneous catalysts, because the single atom nature of Rh dissolved in liquid Ga hinders the formation of significant amounts of coke, e. g. by oligomerisation of carbon fragments and excessive dehydrogenation. In the present study, we investigate the coking behaviour of Ga−Rh SCALMS during dehydrogenation of propane in detail by means of high‐resolution thermogravimetry. We report that the application of Ga−Rh SCALMS indeed limits the formation of coke when compared to the Ga‐free Rh catalyst, in particular when relating coke formation to the catalytic performance. Furthermore, the formed coke has been shown to be highly reactive during temperature programmed oxidation in 21 % O2 /He with onset temperatures of approx. 150 °C enabling a regeneration of the Ga−Rh SCALMS system under mild conditions. The activation energy of the oxidation lies in the lower range of values reported for spent cracking catalysts. Monitoring the formation of coke and performance of SCALMS in situ via thermogravimetry coupled with mass spectrometry revealed the continuous formation of coke, which becomes the only process affecting the net weight change after a certain time on stream. Abstract : High‐resolution thermogravimetric analysis coupled with mass spectrometry was employed to study the coke formation during propane dehydrogenation over Supported Catalytically Active Liquid Metal Solutions (SCALMS). Linking the coke analysis by means of temperature programmed oxidation with the catalytic performance data results in a decreased selectivity towards the formation of coke for SCALMS when compared to classical heterogeneous catalysts. In situ analysis of the formation of coke during catalysis provides insight into the evolution of coke during propane dehydrogenation.